(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The aim of this work is focused on nucleation stages with emphasis on the development of intra-granular ferrite morphologies during isothermal austenite transformation in titanium free micro-alloyed steel. Isothermal treatment was carried out in the temperature range 350 to 600οC. These treatments were interrupted at different times between 2 and 1800 s in order to analyze the evolution of the microstructure. Metallographic evaluation was done by using optical and scanning electron microscopy (SEM) enabled determination of the nucleation onset at all treatments and subsequent on the development of intra-granular ferrite of isothermally treated Ti free micro-alloyed steel. The results show that at high temperatures ( 500  C) polygonal intra-granularly nucleated ferrite idiomorphs, combined with grain boundary ferrite and pearlite were produced and followed by an incomplete transformation phenomenon, At intermediate temperatures (450 and 500  C) an interlocked acicular ferrite (AF) microstructure is produced, and at low temperatures (400 and 350  C) the sheave of parallel acicular ferrite plates, similar to bainitic sheaves but intra-granularly nucleated were observed. In addition to sheaf type acicular ferrite, the grain boundary nucleated bainitic sheaves are observed.